Critical Literacy Based Instructional Reading Materials - Tedi Rohadi (Loquen, 2018)
ABSTRACT The study aims at developing and producing a set of instructional materials used as a model of teaching/learning materials of critical reading. The model is developed through stages and procedures of research and development methods. The results of the study show that; a) the existing instructional materials in certain extent referring to students’ and lecturers incompatibility requires variation in terms of new reading approach, skills to be trained, and types of activities; b) the type of critical reading to be developed is critical literacy; c) the models resulted from the study are theoretically and practically eligible and feasible in accordance to a panel of expert judgement; d) the models are empirically proven effective to improve student's skills in reading critically; e) the final models comprise of students learning materials, teachers guidance/manual, and some supporting materials.